-4x-2(-3x+4)=-4

Simple and best practice solution for -4x-2(-3x+4)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x-2(-3x+4)=-4 equation:


Simplifying
-4x + -2(-3x + 4) = -4

Reorder the terms:
-4x + -2(4 + -3x) = -4
-4x + (4 * -2 + -3x * -2) = -4
-4x + (-8 + 6x) = -4

Reorder the terms:
-8 + -4x + 6x = -4

Combine like terms: -4x + 6x = 2x
-8 + 2x = -4

Solving
-8 + 2x = -4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 2x = -4 + 8

Combine like terms: -8 + 8 = 0
0 + 2x = -4 + 8
2x = -4 + 8

Combine like terms: -4 + 8 = 4
2x = 4

Divide each side by '2'.
x = 2

Simplifying
x = 2

See similar equations:

| -1x+2y=-7 | | 3e+12=0 | | 37=5(3x-4)-3 | | -x+2(3x-6)=-7 | | -2(0)-3y=-12 | | 2y+4=3y+16 | | 8x+5x+22=360 | | -2x-3(-2x+4)=-12 | | 4x-10-2x-10-50=180 | | 3a-6b+9c= | | u-5=-21-5u | | f(x)=1nx(x^2-3) | | 5(v+1)-1=3(v-1)+7 | | 2=2x-8+3x | | 0.80*52/12 | | 0.84*52/12 | | X^2-y^2=46 | | 68+2x=-1+80 | | -4f+4=16-2f | | 1+2*(ln(x))-x=0 | | 2(5-x)-6(x-3)= | | 77+1-1x=167+-10x | | 3(X+1)+1=2(2x+1)-3 | | 13-6h=4h+8 | | x=20-1/2y | | y=20-1/2x | | 6(2x+5)+3(2-3x)=X | | 3x-9=x+32 | | -26+3x=39+14x | | 3x+9=31-7x | | 46-3x=-7x | | 4x+2(3x+2)=5+x |

Equations solver categories